Орчуулгын нийтлэг ба соёлын ойлголтын орчуулга: Univerals of translation: The analyze of cultural concept of Mongolian translated fiction - B., Udval (Mongolian Journal of Foreign Languages and Cultures, 2023)
Translation studies has been provided with number of relatively new theoretical controversy,most notably the set of "universal features of translation" proposed by Mona Baker. Universals of translation are linguistic features there are number of features considered to translation method. These features concern simplification, explication, normalization, distinctive distribution of lexical items. In this paper we aimed to make contrastive analyses of Baker’s universals of translation features and other researcher’s guidelines of translation method. And also we are trying to look for opportunities to identify the cultural translation principle by contrastive analyses of Russian and English translation and source text.